Who Can Get More Happiness? Effects of Different Self-Construction and Experiential Purchase Tendency on Happiness - Xie, Aili; Liu, Lianhua; Lyu, Shiqi; Wu, Lijuan; Pan, Wen Tsao (Frontiers in Psychology, 2022)
In the evaluation of consumption effect, scholars have conducted multi-angle exploration and research, while self-construction and experiential purchase propensity, as personality traits, have been ignored in the evaluation of consumption effect. This paper explores the influence of self-construction and experiential purchase propensity on the evaluation of consumption effect in physical purchase and experiential purchase through empirical research. Empirical studies have shown that:(1)Experiential purchase brings more happiness to interdependent self‐construal and physical purchase brings more happiness to independent self‐construal. (2)In experiential purchase, both materialists and consumers with high experiential purchase tendency can obtain higher happiness.